Alkali metal salt modulated visible photocatalytic degradation of tetracycline hydrochloride by g-C3N4: Degradation pathway, mechanism and toxicity assessment - Yujie Jiao; Sujin Lu; Ru Li; Qikai Liu; Yongxia Ma; Fei Fu; Yaqi Mao; Yang Liu (Results in Chemistry)
The frequent occurrence of tetracycline antibiotics in natural water systems poses a substantial risk to aquatic ecosystems and human health. Achieving efficient degradation of tetracyclines in aqueous environments using visible light is therefore of critical importance. In this study, CaCl2-modified melamine precursors were employed to synthesize CaCNx with varied microstructures through molten salt-assisted calcination, enabling high-efficiency visible-light-driven degradation of tetracycline in water. The results indicated that CaCNx demonstrated remarkable catalytic performance in degrading TC-HCl, with CaCN1 synthesized using 1 mol/L CaCl2 in the precursor exhibiting the highest degradation efficiency, achieving a rate 3.58 times greater than that of CN. In the degradation of tetracycline hydrochloride (TC-HCl) by CaCN1, ·O2− was identified as playing a more significant role than ·OH. Furthermore, LC-MS analysis detected seven degradation by-products, which enabled the proposal of a degradation mechanism and two pathways for TC-HCl degradation by CaCN1. Toxicity validation tests revealed that the TC-HCl prodrug caused acute toxicity (p < 0.0001) to Chlorella vulgaris (p < 0.001) and Vibrio fischeri (p < 0.001), whereas its acute toxicity to C. vulgaris (p < 0.01) and V. fischeri (p < 0.01) was significantly reduced following degradation. This study presents a straightforward and efficient approach for visible light-driven degradation of tetracycline in situ within aqueous environments.